Equal pay demonstration, 1969 (1969)
1969 1960-2000 "Equal pay demonstration, 1969" [EP0190], 1969 This demonstration in London on 18 May 1969 was organised by the National Joint Action Campaign Committee for Women's Equal Rights [NJACCWER]. The Committee was formed following the Ford equal pay strike in 1968 and Fred Blake, the Dagenham area organiser of the National Union of Vehicle Builders, was its secretary. The march ended with a rally in Trafalgar Square. This photograph is from the front cover of the July 1969 issue of The Way for Women and Youth, a newspaper published by the Amalgamated Union of Engineering and Foundry Workers.